Benefits and adverse effects of sacubitril/valsartan in patients with chronic heart failure: A systematic review and meta‐analysis - Elodie Charuel; Thibault Menini; Sabrina Bedhomme; Bruno Pereira; Nathalie Piñol‐Domenech; Suzy Bouchant; Rémy Boussageon; Sylvaine Bœuf‐Gibot; Helene Vaillant‐Roussel (Wiley, 2021)
Abstract This review aims to assess the benefits and adverse effects of sacubitril/valsartan in heart failure, with a focus on important patient outcomes. A systematic review was conducted of double‐blind randomized controlled trials (RCTs) comparing sacubitril/valsartan versus a reference drug, in heart failure patients with reduced (HFrEF) and preserved (HFpEF) ejection fraction, published in French or English. Searches were undertaken of Medline, Cochrane Central, and Embase. The primary outcomes were all‐cause mortality and adverse events. From 2 082 articles analyzed, 5 were included. For all‐cause mortality, the absolute numbers for HFrEF (2 RCTs, 4627 patients) were 16% on sacubitril/valsartan and 18% on enalapril, with a risk ratio (RR) of 0.85 [CI = 0.78, 0.93], and 13% vs 14% in with HFpEF (2 RCTs, 5097 patients), with no statistical difference. Under the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach, the evidence for HFrEF patients was of moderate quality. For HFrEF patients, an increased risk of symptomatic hypotension and angioedema (low quality of evidence) was shown. There was no statistical difference for the risk of hyperkalemia or worsening renal function. There was a protective RR (0.50 [0.34, 0.75]) for worsening renal function for patients with HFpEF, with a high quality of evidence despite similar absolute numbers (1.4% vs. 2.8%). To keep in mind for shared decision‐making, sacubitril/valsartan reduces all‐cause mortality in HFrEF patients but for HFpEF further data are needed. Take into consideration the small number of studies to date to assess the risks.